Analysis of ASAS health index and its influencing factors in ankylosing spondylitis: a prospective study based on the population of Chaoshan region - Li, Aikang; Liang, Rongji; Wu, Liangbin; Cai, Minghua; Chen, Jiayou; Gong, Yao; Zeng, Shaoyin (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the health-related quality of life (HRQoL) in ankylosing spondylitis (AS) patients in the Chaoshan region and identify factors influencing the ASAS Health Index (ASAS-HI) to enhance comprehensive AS treatment strategies.MethodsA survey of ASAS-HI was conducted on 82 AS patients from the rheumatology outpatient department of the First Affiliated Hospital of Shantou University Medical College. The Bath Ankylosing Spondylitis Global Score (BAS-G) assessed overall health status, the Ankylosing Spondylitis Quality of Life Questionnaire (AS-QOL) evaluated quality of life, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) measured disease activity, and the Bath Ankylosing Spondylitis Functional Index (BASFI) assessed functional difficulties. Inflammatory markers and patient data were collected, and univariate/multivariate logistic regression analyses were used to explore influencing factors of ASAS-HI.ResultsThe mean ASAS-HI score was 3.52 ± 3.12. ASAS-HI was positively correlated with BASDAI (r = 0.478, p < 0.001), ASDAS-CRP (r = 0.406, p < 0.001), BASFI (r = 0.338, p < 0.002), and BAS-G (r = 0.335, p < 0.002). Patients with ASDAS-ESR ≥ 2.1, ASDAS-CRP ≥ 2.1, and spinal tenderness had significantly higher ASAS-HI scores than others (p < 0.001). Spinal tenderness and radiographic grading were identified as key influencing factors.ConclusionASAS-HI is significantly impacted by disease activity and functional limitations. Early assessment of ASAS-HI is crucial for optimizing disease management in AS patients.